Eruptive vellus hair cyst: Unveiling the diagnostic features - Rashmi Agarwal; B S Chandrashekar; Prarthana B Desai (Wolters Kluwer Medknow Publications, 2020)
Eruptive vellus hair cyst (EVHC) is a rare developmental abnormality of the vellus hair follicles presenting in children and adolescents as multiple, asymptomatic papules over the chest, axillae, and buttocks. Clinically, it can easily be misdiagnosed as comedonal acne, keratosis pilaris, steatocystoma multiplex, syringomas, milia, lichen nitidus, perforating folliculitis, and molluscum contagiosum. Here, we report a 4-year-old girl who was being treated as a case of steroid-induced folliculitis and was later diagnosed with EVHC based on dermoscopic features and confirmed by histopathological examination. Dermoscopy of EVHC shows the presence of homogenous blue areas, round or oval yellowish structures, with occasional erythematous halos and cystic openings in the epidermis. We report this case to emphasize the role of dermoscopy in early diagnosis of eruptive vellus hair cyst which is a rare condition and can be missed easily. Dermoscopy, being a non-invasive and painless diagnostic tool, can prove to be a useful, particularly in children for differentiating EVHC from its mimickers, thus avoiding the need for biopsy.